2020
DOI: 10.3390/ijerph17093130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pornography Use and Demographic Parameters on Sexual Response during Masturbation and Partnered Sex in Women

Abstract: The effect of pornography on sexual response is understudied, particularly among women. A multinational, community-based sample of 2433 women at least 18 years of age completed a 42-item, opt-in questionnaire collecting information on demographic and sexual history characteristics, use of pornography during masturbation, frequency of pornography use, and sexual response parameters. Pornography use and average frequency were compared across demographic variables. We also examined how pornography frequency predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 75 publications
1
17
0
4
Order By: Relevance
“…Of those, one study with a small sample (n = 48) of U.S. women reported that there were no associations between pornography consumption and women's sexual functioning (Berger et al, 2019). Larger studies have revealed links between frequent pornography consumption and more difficulties with reaching orgasm in women (McNabney et al, 2020;Wright et al, 2021).…”
Section: Sexual Functioningmentioning
confidence: 99%
“…Of those, one study with a small sample (n = 48) of U.S. women reported that there were no associations between pornography consumption and women's sexual functioning (Berger et al, 2019). Larger studies have revealed links between frequent pornography consumption and more difficulties with reaching orgasm in women (McNabney et al, 2020;Wright et al, 2021).…”
Section: Sexual Functioningmentioning
confidence: 99%
“…The above hypothesis has purportedly been supported by circumstantial evidence that notes an increasing prevalence of ED among younger men that is correlated with increasing pornography use, both in society at large and within specific study samples [28,29]. Furthermore, several case studies have drawn attention to the fact that some treatmentseeking men who are frequent pornography users have indeed experienced difficulty with sexual performance within the context of their dyadic relationships [25,26]. Such reports have been augmented by a study that showed that among men visiting a urology clinic, a preference for masturbation using pornography over partnered sex was correlated to a lack of satisfactory intercourse [30].…”
Section: Pornography Use and Erectile Dysfunction (Ed)mentioning
confidence: 97%
“…Moreover, in a survey of over 1000 adults in the United States, those who viewed pornography together with their partner reported significantly higher sexual satisfaction and greater relationship dedication than respondents who only watched pornographic content alone [23]. With regard to the self-perception of potential benefits and problems arising from pornography consumption, multinational studies have found that, in some instances, both men and women attributed generally positive effects of pornography on their sex life, attitudes toward sex, and life in general [24]; in another case, more frequent pornography use during masturbation was generally associated with more favorable sexual response outcomes during masturbation and partnered sex in women, while not negatively affecting sexual or overall relationship satisfaction [25].…”
Section: Pornography Use and Relationship Quality/satisfactionmentioning
confidence: 99%
“…Online pornography provides an accessible and affordable way of pursuing sexual gratification (Cooper, 1998). Pornography use is often associated with masturbation (e.g., Carvalheira et al, 2015;McNabney et al, 2020) and can serve different motivations, including seeking pleasure, increasing sexual satisfaction, feeling intimate with a partner, or coping with negative emotions (e.g., Bőthe et al, 2021;Esplin et al, 2021;Grubbs, Wright, et al, 2019;Kohut et al, 2017). There has been a long debate in the literature about the association between pornography use and intrapersonal and interpersonal functioning .…”
Section: Pornography Use During the Pandemicmentioning
confidence: 99%
“…Solitary pornography use has been negatively associated with sexual satisfaction overall (Wright et al, 2018), and for partnered people it has also been associated with worse relational outcomes (e.g., Willoughby et al, 2016;Wright et al, 2017). Using pornography alone is related to masturbation (e.g., Carvalheira et al, 2015;McNabney et al, 2020), which was driven by feelings of boredom and sexual desire when partners were unavailable during the pandemic (Cascalheira et al, 2021;Hille et al, 2021). Hence, partnered and single participants who report increases in solitary online pornography use since the lockdown should report decreases in their sex life quality (H1) and less sexual satisfaction (H2).…”
Section: Current Study and Hypothesesmentioning
confidence: 99%